Methodological foundations of diagnostics of loss of financial stability by construction enterprises - Kovtun , A. (Ways to Improve Construction Efficiency, 2022)
The article is devoted to the development and justification of improved methodological approaches to diagnosing the loss of financial stability of construction enterprises. The approaches used are not purely "traditional" financial analysis, but focusing on the semantic analysis of the conditions of economic activity and an a priori approach to the study of cause-and-effect relationships. This allows not only to state the financial condition, but also to predict its changes and identify early signals of destabilization. Traditional indicators of solvency and net cash flow are supplemented by an in-depth analysis of the structure of cash flows, in particular, by distinguishing flows from financial, operating and investment activities. It is emphasized that a negative net cash flow from investment activities is a normal and desirable phenomenon, indicating the renewal of fixed capital. In contrast, a positive balance of investment flow, which instead of accumulating potential leads to its "washing out", is considered an indicator of the loss of financial well-being.The article proposes to focus on two key indicators that allow comprehensively highlighting the problems of financial development and the reserves for their solution:Integral financial balance ratio. This indicator is designed for tactical diagnostics and assessing the ability of the construction business to repay current financial obligations in a timely manner. It combines various aspects of balancing free cash, taking into account their significance for the long-term crisis-free implementation of the main activity. This provides a more objective assessment of the threats and risks of tactical management compared to simple liquidity ratios.The monetary equivalent of the intrinsic value of the business for a stakeholder. Designed for strategic financial diagnostics, this indicator is a reasonable monetary amount determined taking into account the most effective use of capital. It is based on an analysis of the asset structure (which should correspond to successful industry benchmarks), typical dynamics of financial results and established trends in the economic environment. In the conditions of a limited market for corporate shares in Ukraine, where the concept of "market value" is often inappropriate, "value in use" serves as a target indicator. This indicator allows assessing long-term financial sustainability and development potential, taking into account the realities of the domestic business environment. The proposed formula for calculating GEVC takes into account fixed costs and the peculiarities of financing long-term investments, assuming a 7-year cycle of fixed capital renewal.